Glomalin-related soil protein enhances the sorption of polycyclic aromatic hydrocarbons on cation-modified montmorillonite. (November 2019) - Chen, Shuang; Sheng, Xue; Qin, Chao; Waigi, Michael Gatheru; Gao, Yanzheng
Abstract: This study investigated the sorption of phenanthrene (as a representative PAH) by cation-modified montmorillonites (Ca-MMT and Fe-MMT) under the influence of Glomalin-related soil protein (GRSP) fractions (EE-GRSP and T-GRSP). Batch sorption studies were carried out as a function of GRSP concentrations (0–500 mg/L), results suggested that the sorption capacities of Ca-MMT and Fe-MMT for phenanthrene were greatly enhanced. The phenanthrene sorption isotherms were in good agreement with the Linear and Freundlich models ( R 2  = 0.886–0.999). The K d values increased from 4.14 to 60.76 L/kg for Ca-MMT and from 15.57 to 153.80 L/kg for Fe-MMT with the GRSP concentrations adding from 0 to 500 mg/L, respectively. Furthermore, the sorption of phenanthrene was higher on Fe-MMT than that on Ca-MMT. It is believed that GRSP developed a higher sorption level on Fe-MMT, resulting in higher phenanthrene sorption. Microscopic and Spectroscopic analyses confirmed that the effects of GRSP on phenanthrene sorption were attributed to the changes in the surface structure and the hydrophobic property of montmorillonites. In the sorption process, GRSP may sorb onto montmorillonites through cation-π interaction when a bridge linkage was formed, and phenanthrene bound with GRSP mainly via π-π electron donor-accepter interaction. The findings could provide an in-depth understanding of the ecological functions of GRSP and provide new insights into the pathways of PAH transport and fate in the contaminated fields. Graphical abstract: Unlabelled Image Highlights: As glue-like protein, GRSP could bind or sorb large quantities of phenanthrene. GRSP facilitated phenanthrene sorption by montmorillonites in a GRSP-concentration dependent manner. GRSP binding changed the surface structure and hydrophobic property of montmorillonites. Findings provided insights into ecological functions of GRSP in PAH-contaminated environments.